Why Uruguay legalized marijuana? The open window of public insecurity. (22nd January 2019) - Queirolo, Rosario; Rossel, Cecilia; Álvarez, Eliana; Repetto, Lorena
Abstract: Background and aims: In 2013, Uruguay became the first country in the world to fully regulate its marijuana market. This ambitious policy was also an unexpected one: none of the usual explanations for legalization of marijuana in other contexts was present in the Uruguayan case. This paper offers an explanation of why Uruguay legalized marijuana. Drawing on Kingdon's theoretical approach, we argue that a window of opportunity opened in mid‐2012, making it both necessary and possible for the government to move towards legalization. Methods: A congruence case study using evidence from a series of interviews with political actors and policy makers, media reports and official documents. Results: There is evidence that marijuana legalization was possible in Uruguay because of the coincidence of a demand for more public safety (problem stream) with the presence of pro‐legalization leaders in strategic political positions (policy stream) and a favorable political environment (political stream) Conclusions: Applying Kingdon's theory of windows of opportunity, Uruguay may have moved towards full regulation of its marijuana market in 2013 because of the convergence of a specific set of problem, policy and political circumstances in May 2012.